A Sense of Place: Climate Change and Resilience in a Small Community - Carver, Audrey C. (Tufts Archival Research Center, 2022)
My thesis was a way of understanding the impact of climate change in my hometown. I used interviews, research, and paintings to explore the social and emotional aspects of drought and wildfire on the residents of my small community. Besides learning more about the wildfire regime and its impacts on the ecosystem, I also learned a lot about indigenous stewardship, anthropological frameworks of person/place relationships, and the psychological impacts of changing landscapes.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Center for Interdisciplinary Studies.